A New Experimental Polytrauma Model in Rats: Molecular Characterization of the Early Inflammatory Response. (29th February 2012) - Weckbach, Sebastian; Perl, Mario; Heiland, Tim; Braumüller, Sonja; Stahel, Philip F.; Flierl, Michael A.; Ignatius, Anita; Gebhard, Florian; Huber-Lang, Markus
Abstract : Background . The molecular mechanisms of the immune response after polytrauma are highly complex and far from fully understood. In this paper, we characterize a new standardized polytrauma model in rats based on the early molecular inflammatory and apoptotic response. Methods . Male Wistar rats (250 g, 6–10/group) were anesthetized and exposed to chest trauma (ChT), closed head injury (CHI), or Tib/Fib fracture including a soft tissue trauma (Fx + STT) or to the following combination of injuries: (1) ChT; (2) ChT + Fx + STT; (3) ChT + CHI; (4) CHI; (5) polytrauma (PT = ChT + CHI + Fx + STT). Sham-operated rats served as negative controls. The inflammatory response was quantified at 2 hours and 4 hours after trauma by analysis of "key" inflammatory mediators, including selected cytokines and complement components, in serum and bronchoalveolar (BAL) fluid samples. Results . Polytraumatized (PT) rats showed a significant systemic and intrapulmonary release of cytokines, chemokines, and complement anaphylatoxins, compared to rats with isolated injuries or selected combinations of injuries. Conclusion . This new rat model appears to closely mimic the early immunological response of polytrauma observed in humans and may provide a valid basis for evaluation of the complex pathophysiology and future therapeutic immune modulatory approaches in experimental polytrauma.